Schola Aquitanica (1583): Latin grammar and Renaissance tradition - Santos, Melyssa Cardozo Silva dos (Revista da ABRALIN, 2021)
The main objective of this article is to make a discussion on the category of analysis of linguistic thought (SWIGGERS, 2013), having as an object of studies the period of Portuguese Renaissance humanism. To develop this investigation, my theoretical and methodological model is derived from the discipline of Historiography of Linguistics (KOERNER, 1996, BATISTA, 2019). Thus, my specific objective is to analyze the current of thought of Portuguese Renaissance humanism from a specific textual source, the document known as Schola Aquitanica, published in 1583. This document is a school regiment with the didactic orientation of classes and methods to teach humanities, used at the Collège de Guyenne in the 16th century. His editio princeps is entitled Schola Aquitanica (SANTOS, 2021), having as author Élie Vinet (1509-1587), a French humanist. However, in the 16th century edition, there is a more specific internal title: Docendi Ratio in Ludo Burdigalensi (the order of studies at the College of Bordeaux), which is also known in French as Le Programme d’Études du Collège de Guyenne (the program of studies at the College of Guyenne)